Social Networking Sites and Political Campaigns in a Pandemic: An Assessment of Ghana’s 2020 Presidential Elections - Sabah, Philip Kwame (UniMAC - GIJ, 2021)
The study assessed the role of social networking sites in political campaigns in a pandemic era. The focus was on n the 2020 general elections in Ghana. This study had as its main objectives, an assessment of the motivation for the use of social networking sites in political campaigns by political parties, assessing the strategies of the political parties in their use of social networking sites in political campaigns, an examination of the political uses of social networking sites by the electorates, and finally, an assessment of the role of social networking sites in the voting decisions of the electorates in the 2020 elections. This study employed the mixed method approach, where a survey was conducted involving 150 respondents and a semi structured interview was done using two representatives of the political campaign teams of the NPP and NDC. The findings of the study showed that the elections which was during the time of a world pandemic saw the increased prioritization of social networking sites by the political parties who strategized various ways of using it since physical political campaigns had been affected by the pandemic. The findings also showed that social networking sites was highly used by the electorates during the 2020 elections as a medium of political participation. The role played by social networking sites in the 2020 election was that it served as a tool for political information, participation, and political voice.
THESIS